2022
DOI: 10.14569/ijacsa.2022.0131168
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspective on Sustaining Education and Promoting Humanising Education through e-Learning

Abstract: The COVID-19 pandemic has shifted the education sector towards an e-learning approach to sustain education. Sustaining student education through e-learning significantly impacts student learning experiences and outcomes, which can be influenced by e-learning infrastructure, e-learning materials, and learning engagement. The concept of humanising education refers to the learning process that reflects students' moralities and values. Focus group discussion is a practical approach to assess students' perspectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Over time, research over a year of distance learning has shown that these experiments were successful for distance learners and the platforms provided a type of interactive platform that met the needs of universal modern education systems. This also led to emerging modes of learning that all institutions sought to adopt at the local level for their faculty and learners [25]. The service-oriented platforms received positive reviews and feedback worldwide, becoming a virtual education workplace that developed new trends in the global education system.…”
Section: Smart Classroom Integration For Language Learning Purposesmentioning
confidence: 99%
“…Over time, research over a year of distance learning has shown that these experiments were successful for distance learners and the platforms provided a type of interactive platform that met the needs of universal modern education systems. This also led to emerging modes of learning that all institutions sought to adopt at the local level for their faculty and learners [25]. The service-oriented platforms received positive reviews and feedback worldwide, becoming a virtual education workplace that developed new trends in the global education system.…”
Section: Smart Classroom Integration For Language Learning Purposesmentioning
confidence: 99%